Radiation Exposure Decreases the Quantity and Quality of Cardiac Stem Cells in Mice. - Lan Luo; Yoshishige Urata; Chen Yan; Al Shaimaa Hasan; Shinji Goto; Chang-Ying Guo; Fang-Fang Tou; Yucai Xie; Tao-Sheng Li (PLoS ONE)
Radiation exposure may increase cardiovascular disease risks; however, the precise molecular/cellular mechanisms remain unclear. In the present study, we examined the hypothesis that radiation impairs cardiac stem cells (CSCs), thereby contributing to future cardiovascular disease risks. Adult C57BL/6 mice were exposed to 3 Gy γ-rays, and heart tissues were collected 24 hours later for further experiments. Although c-kit-positive cells were rarely found, radiation exposure significantly induced apoptosis and DNA damage in the cells of the heart. The ex vivo expansion of CSCs from freshly harvested atrial tissues showed a significantly lower production of CSCs in irradiated mice compared with healthy mice. The proliferative activity of CSCs evaluated by Ki-67 expression was not significantly different between the groups. However, compared to the healthy control, CSCs expanded from irradiated mice showed significantly lower telomerase activity, more 53BP1 foci in the nuclei, lower expression of c-kit and higher expression of CD90. Furthermore, CSCs expanded from irradiated mice had significantly poorer potency in the production of insulin-like growth factor-1. Our data suggest that radiation exposure significantly decreases the quantity and quality of CSCs, which may serve as sensitive bio-parameters for predicting future cardiovascular disease risks.